Freedom of Expression and Parody in Intellectual Property Rights - Marciani Burgos, Betzabé Xenia (2004)
This article takes an approach to parody and its implications for intellectual property law, with a particular focus on copyright and trademark law, highlighting the relevance of its scope in the context of freedom of expression. Within this framework, the authors address the main debates on parody in both the continental intellectual property system and the North American copyright system. On the basis of this analysis, they evaluate the problem in the Peruvian context, where they highlight the progress made in copyright law, but also point out the existing deficiencies. Consequently, this work provides relevant criteria that allow us to understand the scope and limitations of parody in relation to intellectual property rights and freedom of expression.